If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-m=m+2
We move all terms to the left:
6-m-(m+2)=0
We add all the numbers together, and all the variables
-1m-(m+2)+6=0
We get rid of parentheses
-1m-m-2+6=0
We add all the numbers together, and all the variables
-2m+4=0
We move all terms containing m to the left, all other terms to the right
-2m=-4
m=-4/-2
m=+2
| ∠A=7x+24∘∠B=3x+92∘ | | X/2+y/4=1 | | -1+2a=2a-1 | | 56=v/4 | | 5x+8=15x-2 | | -2+6p=88 | | 4(x+4)-10=2x+14= | | n-8/2=4 | | x-67+x-73=60 | | m=8(7,7) | | 2-4m=2m-4m | | 20v-18v+4=16 | | -1=3=2y | | 6-(-2x)=8 | | 5w+15=75 | | 3m-4m=-8+3m | | -3=-7+u | | x=130x | | 5/4m=-10 | | (2n+12)=(3n+18) | | x-0.25x-2-3=4 | | 3X+12y=262.5 | | 12y+28=48 | | 2(2x-1)=124 | | 8x-24+11=19 | | 26-17=3(x-5) | | 24=2u-12 | | -72=-2k+4(4k-4) | | (10)(1/2x(4)=-40 | | 4x+4=-3+2x+11 | | 2(q+-1=6 | | 4u^2+5u-9=0 |